Greater soil carbon losses from secondary than old-growth tropical forests - Raczka, Nanette C.; Ho, Qian Yi; Srinivasan, Vupasana; Lee, Ming Yang; Ko, Chung-Wing; Königer, Madeleine; Chua, Terence; Binny, Delia; Ngo, Kang Min; Andersen, Kelly M. (Frontiers in Forests and Global Change, 2023)
Tropical forests play a crucial role in mediating the global carbon cycle and climate. Southeast Asian tropical forests are experiencing ongoing threats of deforestation and degradation. There is an urgent need to determine how the conversion from primary forest to secondary forest coverage may impact C stocks and cycling. While old-growth forests typically contain larger stores of C aboveground than secondary forests, past research has found varied results for belowground soil C storage and fluxes between tropical forest types. We examined differences in annual soil C efflux in a 2-ha old-growth and an adjacent 2-ha 70-year-old secondary ForestGEO plots in Bukit Timah Nature Reserve in Singapore. We hypothesised that the secondary forest would have greater soil C efflux rates than the old-growth forest and explored several potential drivers of soil C efflux including abiotic and biotic factors such as soil moisture, fine root biomass, and ectomycorrhizal association. We found that the hypothesis was supported, suggesting that belowground carbon dynamics fundamentally differ with forest age. Additionally, we found that fine root biomass was the best predictor of soil C efflux in the secondary forest and soil moisture in the oldgrowth forest. The difference in soil C efflux between forest types indicates that with continued degradation of old-growth forests in Southeast Asia, conversion of old-growth forests into secondary forests may drive greater C loss from soils even after 70 years of regrowth.